REVITALIZATION OF THE ENVIRONMENTAL SUPERVISION POLICY ON COORDINATION AND COMMITMENT BASED COAL MINING - Nurul Listiyani; Rizka Zulfikar; Rakhmat Nopliardy (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2021)
This study was conducted to find a form of control policies on environmental management for mining of coal that regulate the coordination between stakeholders, authorities and the object of supervision, as well as a commitment to an active role between the government, business actors and the community in monitoring environmental management. The approach method in this research is socio-juridical, with qualitative and quantitative analysis methods. The results showed that both from the regulatory and implementation aspects, the coordination of the implementation of supervision had not been regulated and implemented optimally, so that it did not support the realization of an integrated environmental management supervision based on the principle of integration. Based on this, it is necessary to establish a legal system for environmental management in the form of regional regulations which contain an integrated supervisory system with a shared commitment between the leading sector